Fungus-feeding thrips in Iran with a new species of Stictothrips (Thysanoptera: Phlaeothripidae) - Hakimara, Mahsa; Minaei, Kambiz; Sadeghi, Saber; Mound, Laurence (Zootaxa, 2019)
An illustrated key is provided to distinguish 13 genera of fungus-feeding thrips recorded from Iran in both subfamilies of Phlaeothripidae (Idolothripinae, Phlaeothripinae). Information is provided concerning 16 species recorded from this country. A curious new species of Stictothrips is described from both sexes collected from dead leaves in Fars province, southern Iran.